THE EFFECTS OF STUDENT TEAM-ACHIEVEMENT DIVISION COOPERATIVE LEARNING AND DIRECT INSTRUCTION ON STUDENTS' READING COMPREHENSION LEVELS - Suarman, Asep (2013)
Reading is very important for the students' life and language learning. It can be taught through several methods of teaching, two of which are Student Team Achievement Division Cooperative Learning (STAD CL) and Direct Instruction (DI). This study investigated how STAD CL and DI are implemented in a classroom; which one was more effective in improving reading comprehension and comprehension levels (literal, inferential and evaluative) and how the students responded to STAD CL or DI. It was conducted in Grade VIII of junior high school in Serang Regency, Banten Province. It involved 64 participants assigned into two intact groups, each of which was 32 students. One group was taught through STAD CL and another was through DI. The study employed triangulation mixed method design (Creswell, 2003 p. 213; 2008 pp. 558-9), embracing the characteristics of quasi experimental and survey designs. The data were obtained from participant observation, tests, questionnaire and interview. It was found that though in several aspects STAD CL and DI were similar, preparing and ending STAD CL were more demanding for the teacher than those of DI. In the implementation, STAD CL made the teacher more relaxed since the teacher only monitored and gave feedback to the students' teams, not to individuals as he did in DI. From the tests, it was found that STAD CL was more effective than DI in improving their reading comprehension. This can be seen from the t-value (t = .196, df.= 61, p =.333) which was more than the alpha (.05). It was also revealed that the students in STAD CL groups outperformed those in DI in terms of literal and evaluative comprehension levels. This can be seen from the result of the t-test of the post test scores showing that t-values on literal comprehension level (t=.155, df.= 61 p = 6.383) and evaluative level (t=.131, df.= 60 p = 2.345) were more than the alpha (.05). However, on inferential level, there was no significant difference of the groups on the post test with the t-value was .033 (d.f. 61, p = .72), was less than the alpha. Regarding the students' responses, both groups considered STAD CL or DI assisted them in attaining inferential comprehension more than that of literal and evaluative ones. This can be seen from the questionnaire wherein the mean scores of inferential level were higher than those of literal and evaluative comprehension level. It was also revealed that the students in both groups were helped to reach the comprehension levels when being modeled the reading strategies, reading texts and doing guided exercises. Additionally, the students in STAD CL considered they were helped when having team discussion. Finally, it was found that the reward in STAD CL could motivate most students to cooperate within their teams and to compete with other teams; meanwhile that in DI could only motivate high achievers. Due to the limitations, it is recommended that similar future research should involve more comprehension levels/skills, take the teacher's perception into account, and use more items, more teachers and more students. It also should be cautious in grouping students and obtaining similar pre-existing ability on all comprehension levels.